Driver Predictions and Energy Consumption in Car-following Model with BFL Effect - Sunita; Meenkashi; Redhu, Poonam (Communications in Mathematics and Applications, 2023)
In real life, there is a significant role of neighboring vehicles as well as driver’s behavior in the nonlinear dynamics of traffic flow. Based on the car-following model, we examined the impact of individual expectations on a single-lane highway with a Backward-Forward Looking (BFL) effect on traffic flow. The model’s stability criterion is determined through linear and nonlinear analysis, and it is observed that the prediction parameter not only reduces the unstable region but is also helpful in reducing energy consumption. Moreover, it is also remarked that the driver’s prediction effect will become more effective in the case BFL model. Furthermore, the numerical simulation demonstrates that the new model effectively enhances stable regions and it should be considered during the modeling of traffic flow.